IQGAP1-dysfunction leads to induction of senescence in human vascular smooth muscle cells. (September 2020) - Grabowska, Wioleta; Achtabowska, Natalia; Klejman, Agata; Skowronek, Krzysztof; Calka, Malgorzata; Bielak-Zmijewska, Anna
Highlights: IQGAP1 is present in cellular bridges wherein it co-localizes with actin. Direct intercellular communication occurs preferentially between senescent cells. IQGAP1 dysfunction can induce senescence. Abstract: Cell senescence – an irreversible proliferation arrest – is one of the possible cellular responses to stress. There is a vast variety of stimuli, extrinsic and intrinsic, known to induce senescence, and several molecular pathways involved in the process; yet much still remains to be explained. Senescent cells can communicate with neighboring cells through secreted factors such as cytokines and chemokines. Several years ago it was shown that cells can also communicate in a more direct manner by an exchange of proteins via cellular bridges (CBs). Recent studies show that in senescent cells the intensity of such transfer increases. The research also revealed that Cdc42 and actin polymerization are indispensable for this process to occur. Here, we evaluate the hypothesis that, apart from actin and Cdc42, also IQGAP1 could be involved in direct intercellular communication. Our results showed that direct transfer occurred preferentially between senescent cells and that IQGAP1 was not essential for this process. Interestingly, cells harboring mutated IQGAP1 had altered morphology and were characterized by decreased proliferation, increased time of division and appearance of some senescence markers (increased activity of senescence-associated β-galactosidase and induction of senescence-associated secretory phenotype). Our findings suggest that IQGAP1 dysfunction can induce senescence.